2004
DOI: 10.1023/b:boli.0000016613.75677.05
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous acute intermittent porphyria in a 7‐year‐old boy with massive excretions of porphyrins and porphyrin precursors

Abstract: A 7-year-old boy demonstrating hepatosplenomegaly, mild anaemia, mild mental retardation, yellow-brown teeth and dark red urine had excessively elevated levels of urinary delta-aminolevulinic acid, porphobilinogen and uroporphyrin. Furthermore hepta-, hexa-, penta- and copro(I)porphyrins were highly increased in urine. This pattern of porphyrin precursor and metabolite excretion is characteristic of acute intermittent porphyria. The decreased copro(III)/copro(I+III) ratio, normally not found in acute intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Urinary levels of ALA and PBG dramatically decreased following each infusion but failed to reach reference intervals. AIP diagnosis in our patient was confirmed by DNA analysis, which also excluded other possible abnormalities in other genes of heme synthetic pathway [15]. The dissociation between clinical and biochemical outcome emphasizes uncertainties in pathological issues of AIP.…”
Section: (Section B)supporting
confidence: 60%
“…Urinary levels of ALA and PBG dramatically decreased following each infusion but failed to reach reference intervals. AIP diagnosis in our patient was confirmed by DNA analysis, which also excluded other possible abnormalities in other genes of heme synthetic pathway [15]. The dissociation between clinical and biochemical outcome emphasizes uncertainties in pathological issues of AIP.…”
Section: (Section B)supporting
confidence: 60%
“…Visible pigmentation as a result of uroporphyrin also occurs in some annelids [ 62 ], mammalian teeth [ 63 , 64 ], the eggshells of some bird species [ 65 , 66 ] and in the integument of some terrestrial and marine gastropods lacking shells. As a result of these occurrences it has been suggested that the deposition of uroporphyrin is closely connected with calcium metabolism [ 67 ], even though it is also known to occur in invertebrate integument and vertebrate skin.…”
Section: Discussionmentioning
confidence: 99%
“…With elder genetic relatives of patients with acute intermittent porphyria, an analysis of their DNA could be helpful if their urinary excretion of porphyrin precursors and porphyrins is equivocal. A case of a young boy with homozygous acute intermittent porphyria and excessive excretion of urinary haem precursors has been reported (Hessels et al 2004). His parents were shown to be gene carriers.…”
Section: Discussionmentioning
confidence: 99%